The 1958 New York Convention on the Recognition and Enforcement of Foreign Arbitral Awards. - Hammash, Abdelsalam; AlShakhanbeh, Khaled (Advances in Social Sciences Research Journal, 2017)
Arbitration has been preferred as a most convenient procedure to settle economic disputes to prevent legal procedures that may cause harmful conditions for prosperity and profits. Accordingly, the conclusion of the 1958 New York Convention has been the pinnacle of this new form of regulating between parties that may dispute on economic issues rather than relying on the traditional legal procedures. Basically, the Convention has been set up as an International Convention between contracting States to regulate the recognition and enforcement of International arbitral awards. Our research will analyze the provisions of the Convention and its limitations when it has to do with contracting States’ national legal system.